The Evaluation of IT Systems in the Enterprises - Szplit, Marcin (Ocena wdrożenia i funkcjonowania systemu IT w przedsiębiorstwach, 2023)
IT systems have become essential for businesses of all sizes, providing a centralized database of customer, product, and service information that can be used to generate reports and improve efficiency. IT systems also include features such as document management, automated correspondence, data protection, and process tracking and optimization. This study aimed to investigate the relationship between corporate strategy and IT system implementation. The authors observed that IT is becoming increasingly critical to business success. The authors developed a group of variables to quantify the dimensions of various potential situational and organizational conditions that could impact the effective implementation of IT systems supported by business process management (BPM). They then derived the actual conditions that have an impact on effective IT implementation from the group of potential conditions. The results of the statistical analysis confirmed a relationship between the occurrence of changes in the company’s general strategy and the implementation of IT. Companies that made changes to their general strategy in response to the challenges presented by IT were more likely to be satisfied with the accomplished objectives of the implementation. The study’s findings suggest that corporate strategy is an important factor in the success of IT system implementation. Companies that align their IT strategy with their overall business strategy are more likely to achieve their desired outcomes.
Szplit, M. (2023). The Evaluation of IT Systems in the Enterprises. In M. Hajdas (Ed.), Game Changers in Management (pp. 72-79). Publishing House of Wroclaw University of Economics and Business.
Keywords: IT system; strategy; success factors; business process management; ERP; system informatyczny; strategia; czynniki sukcesu; zarządzanie procesami biznesowymi